2021
DOI: 10.1007/s13105-021-00857-2
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of cancer-associated fibroblasts in drug screening assays to evaluate pancreatic cancer resistance to therapeutic drugs

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterised by a pro-inflammatory stroma and multi-faceted microenvironment that promotes and maintains tumorigenesis. However, the models used to test new and emerging therapies for PDAC have not increased in complexity to keep pace with our understanding of the human disease. Promising therapies that pass pre-clinical testing often fail in pancreatic cancer clinical trials. The objective of this study was to investigate whether changes in the drug-dosing regimen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Similar to our results, Monteiro et al prepared an in vitro PDAC multicellular model with a ratio of mouse PDAC cells to human CAF ratio of 8:2 [ 32 ]. Another study reported that an increase in the CAF ratio could ultimately affect the susceptibility of tumor models to anticancer agents [ 33 ]. Since we aimed to see tissue level changes by environmental stress and fibrosis signaling stimulation, we determined the cell ratio that can maximize the phenotype of each cell component as the spheroid formation ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our results, Monteiro et al prepared an in vitro PDAC multicellular model with a ratio of mouse PDAC cells to human CAF ratio of 8:2 [ 32 ]. Another study reported that an increase in the CAF ratio could ultimately affect the susceptibility of tumor models to anticancer agents [ 33 ]. Since we aimed to see tissue level changes by environmental stress and fibrosis signaling stimulation, we determined the cell ratio that can maximize the phenotype of each cell component as the spheroid formation ratio.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the standard-of-care treatment paclitaxel, for which IC 50 values in the low nanomolar range are reported [33], compounds 1 and 4 display only moderate cytotoxic efficacy levels, with IC 50 values of 25.8 and 23.4 µM, respectively.…”
Section: Compound Ic 50 (±Sd) [µM]mentioning
confidence: 81%
“…We can, however, not exclude that, we may have missed more discrete beneficial effects of some of the tested treatment strategies since many factors play a role in the cell cycle regulation and thus proliferation [ 46 , 47 ]. We can also not exclude that the intracellular delivery of the nutrients, the chosen dosages or the possible metabolization in our disease model (fibroblasts) was not optimal and that those therapies might have a positive effect on other symptoms or in other disease models [ 48 ].…”
Section: Discussionmentioning
confidence: 99%